The economic impact of tourism in Peru 1990 - 2015 - Marsano Delgado, José Manuel Enrique (2017)
The article analyzes and evaluates the macroeconomic performance of the tourism sector in Peru betweenthe years 1990 - 2015, with special attention placed in the growing economic importance of its service sector,and its development prospects for the period 2016-2019. The analysis and evaluation are based onquantitative information from the Tourist Data Bank of Peru (Badatur Peru), Tourism Observatory of Peru.